Teachers' Perspectives on Using YouTube as a Source of Mathematics Learning Assistance: Content Analysis of YouTuber Jerome Polin - Prayitno, Anggar Titis; Sumarni, Sumarni; Lestari, Imeldrif Tri; Nurmalasari, Nurmalasari (PRISMA, 2024)
The aim of this research is to determine students' perceptions of the mathematics teaching style presented via the Jerome Polin YouTube Channel and to determine the mathematical understanding abilities of students who use the Jerome Polin YouTube Channel as a source of mathematics learning. This research is a qualitative descriptive research. The research instruments used by researchers in this study were tests of mathematical understanding abilities and student perception questionnaires. The population in this study were mathematics teachers and high school students in classes X and XI in high schools in Kuningan and Majalengka Regencies. The sample from this research was high school mathematics teachers for class X and XI in high schools in Kuningan and Majalengka districts. Data collection techniques were carried out by administering tests and response questionnaires.The data analysis technique in this research uses a flow model of analysis which includes: data reduction, data presentation, verification and drawing conclusions. The research results showed that students' responses to the use of YouTube in mathematics learning were in very positive criteria, with an average score of 82%. Viewed from all aspects, YouTube videos used in mathematics learning can be used as media in the learning process. Meanwhile, the results of students' mathematical understanding tests showed that the average percentage of indicators of students' mathematical understanding abilities was 51.25% of the maximum value, namely 100%.